Simulated response of St. Joseph Bay, Florida, seagrass meadows and their belowground carbon to anthropogenic and climate impacts. (July 2022) - Lebrasse, Marie Cindy; Schaeffer, Blake A.; Zimmerman, Richard C.; Hill, Victoria J.; Coffer, Megan M.; Whitman, Peter J.; Salls, Wilson B.; Graybill, David D.; Osburn, Christopher L.
Abstract: Seagrass meadows are degraded globally and continue to decline in areal extent due to human pressures and climate change. This study used the bio-optical model GrassLight to explore the impact of climate change and anthropogenic stressors on seagrass extent, leaf area index (LAI) and belowground organic carbon (BGC) in St. Joseph Bay, Florida, using water quality data and remotely-sensed sea surface temperature (SST) from 2002 to 2020. Model predictions were compared with satellite-derived measurements of seagrass extent and shoot density from the Landsat images for the same period. The GrassLight -derived area of potential seagrass habitat ranged from 36.2 km 2 to 39.2 km 2, averaging 38.0 ± 0.8 km 2 compared to an observed seagrass extent of 23.0 ± 3.0 km 2 derived from Landsat (range = 17.9–27.4 km 2 ). GrassLight predicted a mean seagrass LAI of 2.7 m 2 leaf m −2 seabed, compared to a mean LAI of 1.9 m 2 m −2 estimated from Landsat, indicating that seagrass density in St. Joseph Bay may have been below its light-limited ecological potential. Climate and anthropogenic change simulations using GrassLight predicted the impact of changes in temperature, pH, chlorophyll a, chromophoric dissolved organic matter and turbidity on seagrass meadows. Simulations predicted a 2–8% decline in seagrass extent with rising temperatures that was offset by a 3–11% expansion in seagrass extent in response to ocean acidification when compared to present conditions. Simulations of water quality impacts showed that a doubling of turbidity would reduce seagrass extent by 18% and total leaf area by 21%. Combining climate and water quality scenarios showed that ocean acidification may increase seagrass productivity to offset the negative effects of both thermal stress and declining water quality on the seagrasses growing in St. Joseph Bay. This research highlights the importance of considering multiple limiting factors in understanding the effects of environmental change on seagrass ecosystems. Highlights: The GrassLight model simulated future climate and anthropogenic effects on the seagrasses of St. Joseph Bay, Florida. A predicted 8% seagrass decline with rising temperatures was offset by an 11% seagrass expansion with ocean acidification. Anthropogenic changes in water quality were a bigger stressor than temperature and pH, predicting a 21% seagrass decline. Ocean acidification may boost seagrass productivity enough to offset thermal stress and declining water quality effects on seagrasses.